Terson syndrom in course of cerebral aneurysm – clinical assessment - Nowosielska, Agnieszka; Czarnecki, Wojciech; Ząbek, Mirosław (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
40 patients with ruptured cerebral aneurysm were screened by an ophthalmologist for the presence of Terson syndrome (TS) and other forms of ocular haemorrhages. Terson syndrom was found in 10 % of cases and 37,5 % of cases presented other forms of ocular bleeding. The most significant neurological symptom leading to diagnose TS, was coma episode occurring in any moment of clinical observation.